Pengaruh komunikasi dan motivasi terhadap kinerja pegawai - Didi Wandi (Jurnal Integrasi Sumber Daya Manusia, 2022)
This study aims to determine and analyze the effect of communication and motivation on employee performance. This research uses descriptive analytical research with a qualitative approach. The method used in this research is a survey method. Respondents in this study were some of the employees of the BPBD of Serang Regency, which amounted to 76 people. The measuring instrument used in this research is a questionnaire. Analysis of the data used is a regression test using the SPSS version 25 program. The results of hypothesis testing that have been formulated show that both partially and simultaneous communication and motivation have a significant effect on employee performance in the field of emergency handling of BPBD Serang Regency.